Implementasi Kegiatan Project-based Learning Menggunakan Media Loose Parts pada Anak Usia 5-6 Tahun - Uyun, Hanuf Af'idatul; Diana, Diana (Universitas PGRI Semarang, 2023)
AbstractProject-based learning is a benchmark point in the Independent Curriculum, especially in driving schools, which in reality, not all institutions at the early childhood education level have implemented Project-based Learning (PjBL). This study aims to describe implementing PjBL activities using loose parts media in the Independent Curriculum in a driving school in early childhood education. This research method is descriptive with a qualitative approach, using data collection techniques of observation, in-depth interviews, and documentation. Primary data sources are the principal, 4 class teachers, 19 students, and four parents at Hidayatullah Islamic Kindergarten. Secondary data sources are annual work programs, weekly learning tools, school guidebooks, daily assessments, serial photo assessments, school profiles, infrastructure, and photos of PjBL activities. They are using data analysis techniques (1) data collection, (2) data reduction, (3) data presentation, and (4) conclusion making. The results of the study found that implementing PjBL at the early childhood education level provides learner-centered educational services according to the needs of children's play based on ideas and imagination of children using loose parts media in project work with the teacher's role as a facilitator and motivator.Keywords: Early childhood education; implementation; loose parts media; project based learningAbstrakPembelajaran berbasis proyek menjadi titik tolak dalam Kurikulum Merdeka khususnya di sekolah penggerak yang pada kenyataannya belum semua lembaga di jenjang PAUD telah menerapkan Project-based Learning (PjBL). Penelitian ini bertujuan untuk mendeskripsikan implementasi kegiatan PjBL menggunakan media loose parts dalam Kurikulum Merdeka di sekolah penggerak di PAUD. Metode penelitian ini bersifat deskriptif dengan pendekatan kualitatif, menggunakan teknik pengumpulan data observasi, wawancara mendalam, dan dokumentasi. Sumber data primer adalah kepala sekolah, 4 guru kelas, 19 siswa, dan empat orang tua siswa di TK Islam Hidayatullah. Sumber data sekunder antara lain program kerja tahunan, perangkat pembelajaran mingguan, buku panduan sekolah, penilaian harian, penilaian foto berseri, profil sekolah, infrastruktur, dan foto kegiatan PjBL. Menggunakan teknik analisis data (1) pengumpulan data, (2) reduksi data, (3) penyajian data, dan (4) penarikan kesimpulan. Hasil penelitian menemukan bahwa penerapan PjBL pada jenjang pendidikan anak usia dini memberikan layanan pendidikan yang berpusat pada peserta didik sesuai dengan kebutuhan bermain anak berdasarkan ide dan imajinasi anak menggunakan media loose parts dalam pengerjaan proyek dengan peran guru sebagai fasilitator dan motivator.Kata kunci: Pendidikan usia dini; implementasi; media loose parts; pembelajaran berbasis proyek